INTERNET AS AN IDEOLOGICAL STATE APPARATUS - Durniev, Oleksandr; Nekhaienko, Oksana (Scientific Journal of Polonia University, 2023)
This article analyzes the role of the Internet in modern society as an ideological apparatus of the state. The emergence of modern means of communication and mass communication (the Internet, mobile phones, etc.) created the possibility of receiving, storing and transmitting information without the direct participation of various subjects (public associations, authorities, politicians, parties) that impose their perception of the world. The authors consider how the transformation of ideology takes place, how it adapts to the information society. The article proves that ideology, despite certain negative connotations and, as it seemed ten years ago, a partial loss of influence, is still not an anachronism and remains a powerful tool for influencing mass consciousness. The authors analyze the key aspects of the impact of internetization on the formation of social consciousness and values. The article contains the results of a study of the use of the Internet by political forces and powerful groups that use the Internet to spread ideological views and influence citizens. The authors address the issue of privacy policies as dictating the agenda for the perception of various kinds of minorities and inequalities, and at the same time creating conditions for limiting freedom of thought. The main theses of the article are illustrated by individual examples of Internet platforms, such as the social networks “Facebook”, “Instagram”, as well as the streaming platform “Twitch”.